The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1007/s10495-009-0365-3
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-2: controversial killer or checkpoint controller?

Abstract: The caspases are an evolutionarily conserved family of cysteine proteases, with essential roles in apoptosis or inflammation. Caspase-2 was the second caspase to be cloned and it resembles the prototypical nematode caspase CED-3 more closely than any other mammalian protein. An absence of caspase-2-specific reagents and the subtle phenotype of caspase-2-deficient mice have hampered definition of the physiological role of caspase-2 and identification of factors regulating its activity. Although some data implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 184 publications
5
33
0
Order By: Relevance
“…The activation of caspase-2 has been suggested to occur in a high molecular complex, the so-called PIDDosome complex, which contains RAIDD (ribosome-inactivating protein (RIP)-associated ICH/CED3 homologous protein with death domain), and PIDD (p53-inducible protein with death domain), in which expression is highly regulated by p53 (66). Previous studies have demonstrated that the activation of p53 is an upstream of, and required for, the activation of caspase-2 and subsequently, the activation of the mitochondria-mediated apoptotic pathway under oxidative stress (44,57,59,67). In our study we demonstrate that activation of caspase-2 is the major determinant for cell death in EtOH-induced mitochondria dependent pathway.…”
Section: Discussionsupporting
confidence: 69%
“…The activation of caspase-2 has been suggested to occur in a high molecular complex, the so-called PIDDosome complex, which contains RAIDD (ribosome-inactivating protein (RIP)-associated ICH/CED3 homologous protein with death domain), and PIDD (p53-inducible protein with death domain), in which expression is highly regulated by p53 (66). Previous studies have demonstrated that the activation of p53 is an upstream of, and required for, the activation of caspase-2 and subsequently, the activation of the mitochondria-mediated apoptotic pathway under oxidative stress (44,57,59,67). In our study we demonstrate that activation of caspase-2 is the major determinant for cell death in EtOH-induced mitochondria dependent pathway.…”
Section: Discussionsupporting
confidence: 69%
“…Previously reported specificities of caspase-2 were based on combinatorial libraries of short peptide sequences (33,34) or ad hoc substrate identification (28). The COFRADIC N-terminal peptide sorting technique (40,41,59) allows identification of protein cleavage events in native proteomes.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of this exon results in a frameshift leading to the introduction of a premature termination codon (PTC) in the mRNA, creating a short-lived nonsense-mediated decay (NMD) substrate (Solier et al 2005). It is unclear under what circumstances caspase-2S mRNA might be stabilized, and conclusive evidence that it is translated is still lacking (Kitevska et al 2009). In any event, when expressed from cDNA, the truncated product of the caspase-2S mRNA was shown to protect against cell death in some contexts (Wang et al 1994;Droin et al 2001).…”
Section: Caspase-2mentioning
confidence: 99%
“…While the existence of the caspase-2S protein remains to be demonstrated conclusively (Kitevska et al 2009), alignment of caspase-2 gene sequences from multiple organisms reveals that E9 and the sequences flanking it are, in fact, highly conserved throughout vertebrates (in fact, E9 is among the most highly conserved portions of the gene) (Fig. 3A).…”
Section: Caspase-2mentioning
confidence: 99%